Can Ethiopia eliminate malaria? Malaria burden: insights from the pre-elimination era, current challenges and perspectives - Woldesenbet, Dagmawi; Tegegne, Yalewayker; Mussema, Abdulhakim; Tamene, Elias; Mohamed, Kemal; Abebe, Wagaw; Mekuria, Melese; Bogale, Kasahun; Geremew, Habtamu; Shifa, Mufta Muzemil; Tegegne, Mulugeta Aemero (Frontiers in Malaria, 2025)
BackgroundEthiopia has faced a significant burden of malaria, enduring endemic transmission in various regions. Despite concerted efforts spanning years, malaria remains a persistent public health issue, particularly affecting underserved rural communities. Previous developments in vector control, diagnostic capabilities, and treatment protocols have led to notable reductions in malaria morbidity and mortality. However, challenges persist, including the emergence of drug and insecticide resistance, compounded by environmental and demographic factors. Understanding the historical context and contemporary challenges is crucial for navigating Ethiopia’s path toward malaria elimination.MethodsFrom October 2023 to January 2024, a systematic search was conducted across open access journals such as PubMed, EMBASE, CINALH, Web of Science, Global Health, and Google Scholar using MeSH and Emtree terms for malaria. The focus was on challenges of malaria elimination in Ethiopia, such as drug resistance, vectors’ insecticide resistance and the loss of the diagnostic potential of rapid diagnostic kits.Main textRecent trend analyses and World Health Organization reports indicate resurgence in malaria cases in Ethiopia. Factors contributing to this resurgence include emerging drug resistance, insecticide resistance, and genetic mutations such as single nucleotide polymorphisms. Other challenges include the spreading resistance to effective antimalarial drugs, socio-cultural barriers to malaria elimination, the challenge posed by Plasmodium vivax in elimination efforts, and the occurrence of imported cases in previously low burden areas. To reverse the rising trend of malaria cases, it is necessary to customize intervention strategies through active community engagement, rigorous healthcare infrastructure, and learning from countries that have successfully eliminated malaria.ConclusionWhile past successes are notable, they do not guarantee current progress, highlighting the need for rigorous implementation of strategies and adaptation of intervention methods to ensure the success of malaria elimination efforts. However, recent data suggests a concerning resurgence in malaria cases, potentially fueled by emerging drug and insecticide resistance. To achieve sustained success in malaria elimination, there is an urgent need for continued vigilance, customization of intervention strategies, and robust collaboration between stakeholders to address these challenges effectively.